Environmental education and the more-than-human perspective : What can Finnish Early Childhood Education and Care learn from Sámi pedagogy? - Helenius, Roosa (2024)
This research explored the curricula guiding the Finnish early Childhood education and Care (ECEC) and the Sámi Early Childhood Education and Care. The focus was in looking into what were the core concepts associated with the more-than-human in the curricula and furthermore, what types of relationships could be identified between the human and the more-than-human in them. The theoretical framework of this qualitative case study was situated in critical posthumanist framework and the reflexive thematic analysis (TA) of documents was guided by decolonial and Indigenous methodologies. The onto-epistemological positionality of this research acknowledged the connectedness of human and the more-than-human and the relationality of knowledge systems. The research was conducted from a settler colonial position, and the Indigenous research ethics guided the study. The results showed that the Finnish ECEC discourses of sustainability and environmental education were dominant in the associations with the more-than-human and the relationship between the human and the more-than-human was predominantly anthropocentric. Albeit the National Core Curriculum for ECEC (2022) seemed to shift towards a more holistic relation with the more-than-human. The results also showed that the Curriculum for Sámi Early Childhood Education and Care (2009) embodied the intertwined relationship between the human and the more-than-human, in all aspects of Sámi pedagogy especially through Traditional Ecological Knowledge (TEK).